2002
DOI: 10.1210/jcem.87.4.8360
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Analysis of cAMP Response Element Modulator Protein and Activating Transcription Factor 2 (ATF2) Isoforms in the Human Myometrium during Pregnancy and Labor: Identification of a Novel ATF2 Species with Potent Transactivation Properties

Abstract: There is now extensive evidence to indicate that components of the cAMP signaling pathway are up-regulated in the human myometrium during pregnancy so as to potentiate the maintenance of uterine quiescence until term. In many tissue and cell types, increased signaling of the cAMP pathway results in profound changes in gene expression that are catalyzed via stimulation of PKA and activation of cAMP-dependent transcription factors that bind cAMP response elements (CREs) within the promoter regions of affected ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…As mentioned above, promoter analysis revealed that the Cx43 promoter contains binding sites for AP1 (Geimonen et al 1996;Echetebu et al 1999;Bailey et al 2002). Transfection of cardiomyocytes with an EGFP gene under control of truncated Cx43 promoter revealed that about 50% of the maximal response to phenylephrine could be obtained with a promoter fragment containing only the first 91 bp near the transcription initiation site (TIS) of the promoter (Salameh et al 2008).…”
Section: Role Of α-And β-Adrenoceptors In the Acute Regulation Of Gapmentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned above, promoter analysis revealed that the Cx43 promoter contains binding sites for AP1 (Geimonen et al 1996;Echetebu et al 1999;Bailey et al 2002). Transfection of cardiomyocytes with an EGFP gene under control of truncated Cx43 promoter revealed that about 50% of the maximal response to phenylephrine could be obtained with a promoter fragment containing only the first 91 bp near the transcription initiation site (TIS) of the promoter (Salameh et al 2008).…”
Section: Role Of α-And β-Adrenoceptors In the Acute Regulation Of Gapmentioning
confidence: 90%
“…Furthermore, Cx43 upregulation was accompanied by phosphorylation of p38, ERK1/2 (formerly named p42/44) and JNK, indicating activation of these kinases, and by translocation of the transcription factors AP1, CREB and NFAT to the nucleus (Salameh et al 2009). It is known that AP1, CREB and NFAT binding sites exist in the Cx43 promoter (Echetebu et al 1999;Bailey et al 2002;Glover et al 2003). AP1 is a typical downstream target of the MEK1-ERK1/2-MAPK cascade.…”
Section: Role Of α-And β-Adrenoceptors In the Acute Regulation Of Gapmentioning
confidence: 99%
“…We have previously reported differential expression of specific CREM protein isoforms within the myometrium tissue throughout pregnancy, namely CREM 2␣ and CREM␣ (Fig. 1B), and demonstrated their ability to bind CRE-containing oligonucleotides and activate and/or repress reporter gene transcription (27). Furthermore, through microarray studies, we have recently shown that these potent factors act in myometrial cells to affect the expression of a plethora of genes with defined roles associated with uterine activity during pregnancy (28).…”
mentioning
confidence: 89%
“…CREM appears to be particularly important in the brain, where it has been implicated in the regulation of long term memory and the circadian clock (2); in the testes, where it orchestrates spermatogenesis (23); in the liver, where it plays a role in hepatocyte regeneration (24); in the heart, where it may play a role in cardiac gene regulation (25); and in the uterus, where there is strong evidence for its role in the regulation of uterine contractility (26,27). Europe-Finner et al (19,20) reported an increased level of cAMP in human myometrial smooth muscle cells during pregnancy, potentiated by altered expression of various components of the cAMP signaling pathway, in particular the G protein G␣ s .…”
mentioning
confidence: 99%
“…These include calcitonin gene-related peptide receptors (6) and the adenylyl cyclase stimulatory G protein, G␣s (7)(8)(9)(10)(11)(12)(13), whose levels of expression are considerably increased within the myometrium during gestation, causing an increased production of cAMP and activation of protein kinase A (PKA); these factors are reduced subsequently in labor (7)(8)(9)(10)(11)(12)(13). At present, there is a paucity of data describing how G␣s expression is regulated in any system including the myometrium.…”
mentioning
confidence: 99%